Dänische Forscher bei der Erschliessung der Achaimeniden-Inschriften - Schmitt, Rüdiger
Carsten Niebuhr; Oluf (Olaus) Gerhard Tychsen; Friederich Münter; Rasmus Cristian Rask; Niels Ludvig Westergaard.